The Correlation Between College students’ Reading Anxiety and Their Reading Strategies. - Risanta, Arfan Adji (RETAIN, 2021)
This research aims to explore further about students reading anxiety level and investigate that reading anxiety still exist in university levels, also, finds the most used reading strategy of college students. Subsequently, this present study also investigates the correlation between reading anxiety and the reading strategy students used. The Foreign Language Reading Anxiety Scale (FLRAS) and SORS (The Survey of Reading Strategies Questionnaire) has been conducted on 60 sophomore students in the English department at one of the state universities in Surabaya. The result reported that reading anxiety still exists at university levels, with details 10 students (17%) of the participant are categorized as high groups, 28 students (47%) are categorized as Medium, and 22 students (36%) categorized as low anxiety groups. This research also reports that, Problem-Solving reading strategy (PROB) is the frequently used reading strategy (M=3.702), followed by the Global reading strategy (GLOB) (M=3.63) and the fewest used reading strategy Support reading strategy (SUP) (M=3.39). Additionally, the result shows that there is no correlation between college students reading anxiety and reading strategy in total p=0.99, PROB p=.255, GLOB p=.238, SUP p=.522.